2021
DOI: 10.3390/math9060602
|View full text |Cite
|
Sign up to set email alerts
|

Use of PROMETHEE MCDA Method for Ranking Alternative Measures of Sustainable Urban Mobility Planning

Abstract: One of the most crucial steps during the implementation of a Sustainable Urban Mobility Plan (SUMP) as well the relevant transportation projects is the final measures and policies’ selection that will be realized in order for the plan to achieve the study area targets. There are many methodologies that have been used for a specific purpose, with cost-effective and cost–benefit analysis being the most popular. According to the new specifications of SUMPs, the co-creation and co-planning of the future measures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
0
3
0
1
Order By: Relevance
“…Recently, Duleba et al (2021) suggested a new approach for modal split estimation by ranking mode choice alternatives. Morfoulaki and Papathanasiou (2021) evaluated the most important sustainable mobility measures that should be implemented in urban areas. Rao (2021) defined key sustainability indicators of transportation systems and examined their causality and correlation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, Duleba et al (2021) suggested a new approach for modal split estimation by ranking mode choice alternatives. Morfoulaki and Papathanasiou (2021) evaluated the most important sustainable mobility measures that should be implemented in urban areas. Rao (2021) defined key sustainability indicators of transportation systems and examined their causality and correlation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…AHP/ANP and their hybrids are the most frequently used methods [29][30][31][32][33][34][35]. Moreover, some other MCDM methods have been adopted in research, such as PROMETHEE [36,37], ELECTRE [38,39], DEA [8], etc. In addition to MCDM methods, other approaches have also been used in transport sustainability assessment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The greater homogeneity of approaches responds to the existence of a growing technical literature and greater experience of local administrations in this matter, although, there is still no regulatory technical framework available, as it happens at present in other countries [ 50 , 51 , 52 , 53 ]. Regarding its results, although the time frame to observe them in this case is much shorter, we found an absence of real commitments by local authorities.…”
Section: Discussionmentioning
confidence: 99%